Minimal residual disease detection in autologous stem cell grafts from patients with high risk neuroblastoma. Issue 8 (4th May 2015) - van Wezel, Esther M.; Stutterheim, Janine; Vree, Florentien; Zappeij‐Kannegieter, Lily; Decarolis, Boris; Hero, Barbara; Berthold, Frank; Schumacher‐Kuckelkorn, Roswitha; Simon, Thorsten; Fiocco, Marta; Voermans, Carlijn; van Noesel, Max M.; et al.
Abstract Background The clinical significance of minimal residual disease (MRD) detected by real‐time quantitative PCR (qPCR) in autologous stem cell grafts in high risk neuroblastoma is still controversial. In this retrospective multicenter study, autologous stem cell grafts of a large cohort were studied using a panel of RNA markers. Procedure From 104 patients with high risk neuroblastoma, who received autologous stem cell transplantation as first line treatment, 66 peripheral blood stem cells (PBSC) and 38 CD34+ selected grafts were retrospectively collected at 2 Dutch and 12 German centers between 1997 and 2010. To investigate graft contamination qPCR was performed by using 5 neuroblastoma specific markers (PHOX2B, TH, DDC, CHRNA3, and DBH). Results In PBSC 6/66 (9%) and in CD34+ selected grafts 3/38 (8%) samples were contaminated. Graft contamination was not associated with an unfavorable outcome (5‐years OS, 66% vs. 50.5%; P = 0.6 and 5‐years EFS, 22% vs. 35%, P = 0.7). In multivariate Cox analysis BM MRD at time of harvest was significantly associated with survival (P = 0.008 OS and P = 0.002 EFS), but graft contamination was still not associated with an unfavorable outcome (P = 0.9 OS and P = 1 EFS). Conclusions Graft contamination is very infrequent in this retrospective cohort of patients with no or minimal BM disease prior to stem cell collection and does not influence outcome in univariate and multivariate analysis. The presence of MRD at time of harvest is a strong outcome predictor. However, these results will have to be verified in a large prospective study. Pediatr Blood Cancer 2015;62:1368–1373. © 2015 Wiley Periodicals, Inc.